Gender Differences in Urdu (language) Reading: Evidence from the USAID Funded Pakistan Reading Project (PRP) for Early Grade Students. - Ahmed, Muneer; Atta, Batool; Sarwar, Naveed (JECCE, 2024)
This study aims to explore gender-based differences in reading achievement among elementary students in selected PRP schools in Azad Jammu and Kashmir (AJ&K), Pakistan. Based on descriptive experimental design, data were collected from a stratified random sample of 120 girls and 120 boys in grade II in PRP schools in Muzaffarabad. A reading achievement test was adapted from PRP assessment tools – nine questions addressing lower to higher-order reading skills – was administered. The results were analyzed using PRP’s categorization system specifically developed for Urdu reading assessment of grade II. The study finds no statistically significant gender differences in lower to higher-order reading skills achievement, with boys marginally outperforming girls. Contrary to global trends, gender was not found to be a significant variable in reading achievement in this context. Both genders showed low performance in comprehension, highlighting substantial gaps in the implementation of the PRP initiative. These findings have critical implications for education policy and practice in Pakistan, emphasizing the need for targeted interventions to enhance the effectiveness of foreign-funded educational programs like PRP to address persistent challenges in reading comprehension.